2013
DOI: 10.1186/1471-2458-13-388
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health and seasonal influenza vaccination in adults ≥65 years: a systematic review of qualitative and quantitative data

Abstract: BackgroundVaccination against influenza is considered the most important public health intervention to prevent unnecessary hospitalizations and premature deaths related to influenza in the elderly, though there are significant inequities among global influenza vaccine resources, capacities, and policies. The objective of this study was to assess the social determinants of health preventing adults ≥65 years old from accessing and accepting seasonal influenza vaccination.MethodsA systematic search was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
285
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(339 citation statements)
references
References 68 publications
27
285
3
7
Order By: Relevance
“…18,25 Moreover, our results concur with the concern that accessibility for older adults is not limited to free-of-cost access and includes several dimensions, such as the distance to the health care center, means of transport, and health literacy. 26 The success of vaccination campaigns in the country is supported by the credibility of the Brazilian National Immunization Program. This is recognized by the population due to its results in infant vaccination that led to control and eradication of several diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,25 Moreover, our results concur with the concern that accessibility for older adults is not limited to free-of-cost access and includes several dimensions, such as the distance to the health care center, means of transport, and health literacy. 26 The success of vaccination campaigns in the country is supported by the credibility of the Brazilian National Immunization Program. This is recognized by the population due to its results in infant vaccination that led to control and eradication of several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…12,36,37 Finally, as previously observed, 4,12,18,36-38 vaccine uptake was more prevalent among individuals with chronic diseases. According to the evidence, 26,36 having comorbidities may increase the severity of influenza, possibly making this group more motivated to seek vaccination. In addition, those affected by chronic diseases may have a more intense interaction with health services, which increases the likelihood of being appropriately informed of the beneficial effects of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with chronic diseases may thus have more access to information on vaccination campaigns for the elderly and are more prone to come for vaccination. According to the literature, influenza vaccine uptake in the elderly is related to recommendation by health care professionals and ease of access to health services 10,30,31,34,35 . In Spain, Jiménes-García et al 36 identified higher influenza vaccination rates in elderly with chronic obstructive pulmonary disease who had consulted a physician in the previous year, due to the greater odds of receiving recommendations to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Bu amaç doğrultusunda, mutluluk ve iyi oluş kavramlarına ayrıca önem verilmektedir (3,4). Bu konularla ilgili pek çok çalışmaya zemin hazırlarken, aynı zamanda da elde edilen sonuçlara dayanarak ruh sağlığını korumaya yönelik çeşitli uygulamalar, müdahale yöntemleri geliştirilmektedir (5,6).Bu nedenle müdahale yaklaşımlarından önce mutluluk ve iyi-oluş kavramlarını açıklamakta yarar vardır.…”
Section: Pozitifunclassified
“…Yapılan çalışmalara bakıldığında, mutluluk ve iyi oluş kavramlarının beraber kullanımının yaygın olduğu görülmektedir (3,4,13,14). Diener'in "İyi Oluş Modeli"nde kişinin mutluluğu; kendi hayatını, çevresini ve duygularını nasıl adlandırdığı ile açıklanmaktadır (14).…”
Section: İyi Oluşunclassified